DOI: 10.31274/etd-180810-4521
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and roles of the LuxS system, methyl recycling, and DNA methylation on the physiology of Campylobacter jejuni

Abstract: Introduction iii Materials and Methods Results Discussion Acknowledgements Author Contributions Figures legends Tables CHAPTER 4. CHARACTERIZATION OF THE CJSA_RS00180 DNA METHYLTRANSFERASE IN CAMPYLOBACTER JEJUNI IA3902 Abstract Introduction Materials and Methods Results Discussion Figures legends Tables CHAPTER 5. General Conclusions General Discussion Recommendations for Future Research ix ACKNOWLEDGEMENTS This thesis was made possible by the collective efforts and support of colleagues, friends, and family.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 249 publications
(466 reference statements)
0
2
0
Order By: Relevance
“…The loss of the ability of ΔluxS to sustain colonization in chickens, as demonstrated in this study, has been previously described in IA3902, but the same phenotype was not observed in the closely related NCTC 11168 (8); the reason for this difference is currently unknown but has been speculated to be related to strain-specific differences in the metabolism of methionine or S-adenosylmethionine (SAM) recycling, which are also affected by the luxS mutation (28). Additional work in our lab has shown that the luxS mutation in IA3902 does disrupt the AMC, which functions to recycle SAM and produce methionine (64); however, DNA methylation in IA3902 was not affected by the luxS mutation (65). Comparative genomics reveals that NCTC 11168 does harbor an additional genomic system for methionine biosynthesis in the form of metAB which is not present in IA3902 and may represent an alternative pathway for synthesis of this required amino acid and an explanation for the observed difference in colonization ability.…”
Section: Figmentioning
confidence: 96%
“…The loss of the ability of ΔluxS to sustain colonization in chickens, as demonstrated in this study, has been previously described in IA3902, but the same phenotype was not observed in the closely related NCTC 11168 (8); the reason for this difference is currently unknown but has been speculated to be related to strain-specific differences in the metabolism of methionine or S-adenosylmethionine (SAM) recycling, which are also affected by the luxS mutation (28). Additional work in our lab has shown that the luxS mutation in IA3902 does disrupt the AMC, which functions to recycle SAM and produce methionine (64); however, DNA methylation in IA3902 was not affected by the luxS mutation (65). Comparative genomics reveals that NCTC 11168 does harbor an additional genomic system for methionine biosynthesis in the form of metAB which is not present in IA3902 and may represent an alternative pathway for synthesis of this required amino acid and an explanation for the observed difference in colonization ability.…”
Section: Figmentioning
confidence: 96%
“…The LuxS enzyme is critical for the formation of S-adenosylmethionine (SAM), which is a major methyl donor necessary for methylation of DNA, proteins, carbohydrates and other molecules important to the physiology of prokaryotes (Parveen and Cornell, 2011). It is plausible that expression of this methyltransferase is sensitive to decreased availability of products from the activated methyl cycle due to luxS mutation; however, recent data generated within our lab group suggests that this gene does not encode an active methyltransferase (Mou, 2015).…”
Section: Identification Of Additional Non-coding Rnas In Ia 3902mentioning
confidence: 99%